Comparison of the analgesic efficacy of ultrasound-guided superficial serratus anterior plane block and intercostal nerve block for rib fractures: a randomized controlled trial - Musa Zengin; Onur Küçük; Muhyettin Aslan; Göktürk Fındık; Ali Alagöz (BMC Anesthesiology)
Abstract Background Various regional analgesic methods are frequently incorporated into multimodal analgesia strategies for managing rib fractures. This study aimed to compare the analgesic efficacy of ultrasound-guided superficial serratus anterior plane block (S-SAPB) and intercostal nerve block (ICNB) in patients with isolated rib fractures. Methods This randomized controlled trial included patients aged 18–65 years with unilateral isolated rib fractures (≤ 6 ribs) resulting from trauma. Patients underwent ultrasound-guided S-SAPB (20 ml 0.25% bupivacaine) or ICNB (3 ml 0.25% bupivacaine for each fractured rib). Pain levels were assessed using the Visual Analogue Scale (VAS) both prior to the procedure (Pre-Block, (T0)) and at specific time points following the intervention: 1st hour (T1), 2nd hour (T2), 4th hour (T4), 8th hour (T8), 16th hour (T16), and 24th hour (T24). The changes in observed values over time were expressed as delta (Δ). Results Both S-SAPB and ICNB provided effective analgesia. In the first 4 h, ICNB demonstrated a greater reduction in VAS scores, particularly in patients with 10th and 11th rib fractures. However, S-SAPB resulted in significantly longer-lasting analgesia, with greater pain relief after 8 h (T8–T24) compared to ICNB (p < 0.05). Patients in the S-SAPB group required no additional analgesia, whereas 43.3% of ICNB patients required supplemental tramadol (p < 0.001). Both techniques were well tolerated, with no reported complications. Conclusions S-SAPB provides prolonged analgesia and may be preferable for managing rib fracture pain beyond the initial 8 h. However, ICNB offers superior pain relief in the early postoperative period, especially for lower rib fractures (10th–11th ribs). A combined approach that includes both blocks may optimize pain control in patients with multiple rib fractures involving the 10th and 11th ribs.